Primi approcci a una dinamica formale della mente - Lami, Gabriele (Metapsychologica - rivista di psicanalisi freudiana, 2023)
The topic of this article is the introduction of some key elements to address the discussion of a metapsychological dynamic of the mind. The starting point is Irma’s dream described by Freud in The Interpretation of Dreams. The dream, as it is represented and analyzed by Freud, is a good example of the expression of the dynamics of the mind. Starting from this example are introduced themes such as: the space of the mind, the representations, the concept of distance and force. We then try to correlate the principles of dynamics to the three metapsychological principles of nirvana, pleasure and reality. The final target is to show how the analogies between mechanics and metapsychology are consistent and useful to address a potential formalization of metapsychological dynamics.